PICTURE SERIES AS A MEDIUM TO TEACH WRITING A NARRATIVE TEXT - Sidiq, Rahmat; Rufinus, Albert; Rezeki, Yanti Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research focused on investigating the effectiveness of picture series as a medium to teach writing a narrative text to the tenth grade students of SMAN 7 Pontianak in academic year 2017/2018. It was pre-experimental research and the subjects of the research were thirty four students of X MIA 5. The sample was taken using cluster random sampling technique. The technique of data collection was measurement test. Then, the instruments to collect the data were pre-test and post-test in the form of writing test. The findings showed that the mean score of pre-test was 65.35 and post-test was 72.50. The interval between the pre-test and post-test was 7.15. Based on the data analysis, the effect size was 0.89 and categorized as moderate effect based on the table of effect size. Therefore, the use of picture series as a medium to teach writing a narrative text was considerably effective in which the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected.Keyword: picture series, medium, teaching writing, narrative text